Lamentations in Recent Research (2013-2025) - Walker, Justin (Currents in biblical research, 2025)
The last decade has seen a significant expansion in Lamentations research. Since 2013, over 30 new commentaries and monographs have been published on various topics in this short biblical book, along with dozens of articles and essays. Many of these studies represent extensions of the once ‘new’ trends of the 2000s—literary studies, feminist interpretations, trauma readings, and reception historical studies—while others have pushed Lamentations research into even ‘newer’ territories (iconographic exegesis, performance criticism, intertextual approaches, and so forth). This essay traces these various trends in Lamentations research and surveys many publications from the last decade.